2020
DOI: 10.1007/s10640-020-00445-w
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Nature and the Environment During the COVID-19 Crisis

Abstract: As our behavioral patterns change due to the COVID-19 crisis, our impact on nature and the environment changes too. Pollution levels are showing significant reductions. People are more aware of the importance of access to local green and blue spaces. By analyzing online search behavior in twenty European countries, we investigate how public awareness of nature and the environment has evolved during the COVID-19 crisis. We find that the crisis goes hand in hand with a positive shift in public awareness of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(152 citation statements)
references
References 36 publications
9
138
1
4
Order By: Relevance
“…This is actually a rather inspiring result implying that despite the fact that public risk perception has been raised towards the pandemic, attention to climate change issues has not thus been comprised; to be more speci c, individuals do not talk less with families and friends about climate change, browse or forward climate change related news less frequently in mass media, or rank climate change as less dangerous due to COVID-19 outbreak. This is consistent with Rousseau and Deschacht's research of public online search behavior that before and after COVID-19 became the searching peak in twenty European countries, environment topics such as "CO 2 tax" and "climate change" remained unaffected, though not presenting an increasing trend like that of nature topics 19 . As addressed by existing researches, interpersonal discussion can generate information acquisition of climate change related scienti c facts thereby leading to increased climate change concern 49 and this discussion seems fairly effective among family members in forms of intergenerational learning (IGL) 50 and contagion from wives to husbands 51 but currently remains a promising yet relatively understudied eld.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is actually a rather inspiring result implying that despite the fact that public risk perception has been raised towards the pandemic, attention to climate change issues has not thus been comprised; to be more speci c, individuals do not talk less with families and friends about climate change, browse or forward climate change related news less frequently in mass media, or rank climate change as less dangerous due to COVID-19 outbreak. This is consistent with Rousseau and Deschacht's research of public online search behavior that before and after COVID-19 became the searching peak in twenty European countries, environment topics such as "CO 2 tax" and "climate change" remained unaffected, though not presenting an increasing trend like that of nature topics 19 . As addressed by existing researches, interpersonal discussion can generate information acquisition of climate change related scienti c facts thereby leading to increased climate change concern 49 and this discussion seems fairly effective among family members in forms of intergenerational learning (IGL) 50 and contagion from wives to husbands 51 but currently remains a promising yet relatively understudied eld.…”
Section: Discussionsupporting
confidence: 88%
“…At the individual level, however, limited studies have seemingly controversial insights regarding the effect of the pandemic on climate change attitude. For example, a survey by the pollsters Opinium revealed that 48% of the public claimed that the governments should respond to climate change with same urgency as coronavirus 18 , indicating a moderate public recognition of treating the pandemic and climate change as parallel crises; in contrast, a research using difference-in-differences approach (DiD) comparing the Google Trends search popularity indicator (SPI) before and after March 14 th 2020, when the searching behavior of COVID-19 related topics peaked, discovered a rapid and clear increase in the search for nature topics after this day, but environment topics including CO 2 tax and climate change did not present difference in SPI 19 , which means unchanged concern for climate change with the in uence of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, we did not find any evidence that the COVID-19 crisis affected the environmental attitude. These results are in line with the evidence from recent studies showing that frequency of many pro-environmental behaviors remained the same during the COVID-19 crisis as before the crisis (Čadová, 2020;IPSOS, 2020) and that awareness of and concern about pro-environmental problems remained also the same (Rousseau and Deschacht, 2020). More broadly, our results are consistent with previous findings of the relative stability of environmental attitude (Kaiser et al, 2014).…”
Section: General Pro-environmental Behaviorsupporting
confidence: 93%
“…Under conditions of social distancing, where outdoor recreation is severely reduced and restricted [(Rice et al 2020 ); for Austrian data, see (Google 2020 )], the ability to spend time outdoors is likely to take on added importance vis-à-vis emotional well-being (Burtscher et al 2020 ). Indeed, there is some evidence from Europe that the public are more aware of the importance of spending time in natural environments during the COVID-19 pandemic (Rousseau and Deschacht 2020 ) and that being outdoors was associated with significantly higher positive affect and lower negative feelings (Lades et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%